Participatory Learning With Game Method For Learning Completeness In Islamic Religious Education - Ciptaningsih, Yeni; Rofiq, Muhammad Husnur (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This article aims to explain and find out the application of participatory learning with the game method at MAN 1 Mojokerto and how the application of participatory learning with the game method can improve student learning mastery at MAN 1 Mojokerto? This type of research uses qualitative methods with a descriptive pattern field research approach. This study also uses a participatory learning theory framework, game method theory, and student learning mastery theory. This study came to the findings that 1) participatory learning using the game method, which was realized in the Team’s Games Tournament (TGT) model, combined with planned and guided learning through Lesson Study, could increase students' learning motivation and lead to the achievement of student learning mastery. 2). The application of Teams Games Tournament cooperative learning combined with guided inquiry can improve students' mastery and learning outcomes. It can be seen from the classical learning completeness of students by 53.8%, in the untreated learning, it increases to 96.2% in the planned and guided learning that applies participatory learning with the game method. This increase is due to the application of participatory learning with the game method (Teams Games Tournament) can increase students' learning motivation so that students are easier to understand the material being studied along with optimal student learning mastery.